Fluorine-containing crosslinked solid-state polymer electrolyte, solid-state lithium battery and preparation method of solid-state lithium battery

By adding fluorine-containing crosslinking agent to the polyether-based solid polymer electrolyte to form a three-dimensional network structure and aggregated ion pair, the problem of low stability of existing electrolytes under high voltage conditions is solved, and the high ion conductivity, mechanical properties and high voltage stability is improved, and it is suitable for high-voltage positive electrodes.

CN119833739APending Publication Date: 2025-04-15FUZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411773145.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing polyether-based solid polymer electrolytes are difficult to stabilize under high-voltage conditions, have low electrochemical stability, and are difficult to match with the high-voltage positive electrode.

Method used

By adding 2,2'-(2,2,3,3,4,4,5,5-octafluorohexane-1,6-diyl)bis(ethylene oxide) as the fluorine-containing crosslinking agent, a three-dimensional network structure and aggregation ion pair are formed, which is highly separated from the solvent molecules, improving ion conductivity, mechanical properties and high voltage stability.

Benefits of technology

It achieves high ionic conductivity, good mechanical properties and high voltage stability, extends battery life, and can match with the high voltage positive electrode, improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833739A_ABST
    Figure CN119833739A_ABST
Patent Text Reader

Abstract

The invention discloses a fluorine-containing cross-linked solid polymer electrolyte, a solid lithium battery and a preparation method thereof.The preparation method comprises the steps that firstly, a polymeric monomer, a fluorine-containing cross-linking agent, lithium salt and an initiator are mixed, and an obtained precursor solution is continuously stirred at the normal temperature to form a uniform electrolyte solution; in the electrolyte, the fluorine-containing cross-linking agent and the polymer monomer with the epoxy alkyl functional group are subjected to in-situ polymerization to form the solid electrolyte with a fluorine-containing cross-linking agent three-dimensional network structure. The solid-state lithium battery is a battery containing the solid-state electrolyte. According to the method, the polyether-based solid polymer electrolyte is modified through the fluorine-containing cross-linking agent, so that the fluorine-containing cross-linking agent and the polyether-based solid polymer electrolyte are chemically bonded, the problem of lithium dendrite growth is solved, and the high-voltage resistance and cycle stability of the lithium battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium battery electrolyte materials, and mainly relates to a method for forming a solid electrolyte by adding 2,2'-(2,2,3,3,4,4,5,5-octafluorohexane-1,6-diyl)bis(ethylene oxide) to crosslink long polyether chains. Background Art

[0002] As the energy density of energy storage devices is increasingly pursued, lithium metal anodes have a high theoretical specific capacity (3860mAh g -1 ), the lowest redox potential (-3.04V vs. standard hydrogen electrode), and light weight make lithium metal batteries stand out from many battery systems and become the focus of attention. However, lithium metal batteries still have problems such as poor safety and unstable cycle performance.

[0003] Solid polymer electrolytes using novel in-situ polymerization processes have the potential to prevent the growth of lithium metal dendrites, and can achieve close contact and good stability at the electrode / electrolyte interface. Among the in-situ polymerization systems, polyether-based solid polymer electrolytes have attracted widespread attention due to their good compatibility with lithium metal. Polyether-based solid polymer electrolytes generally include lithium salts and polyether long-chain structures that dissolve lithium salts. The polyether long-chain structures are formed by in-situ polymerization of polymer monomers with alkylene oxide functional groups (such as 1,3-dioxolane (DOL) polymerization to form PDOL), in which lithium salts are responsible for providing anions, while polymer chains provide coordination active sites for lithium ion transport. In lithium-ion batteries, lithium ions form a solvation layer in the electrolyte, and then exchange with polymer chains through the solvation layer, ultimately achieving lithium ion transport. The in-situ polymerization process is incomplete and reversible, and the residual molecular monomers or oligomers may undergo continuous side reactions with the cathode and anode, resulting in increased impedance, capacity degradation, and mechanical property degradation due to the reverse polymerization process, which accelerates the penetration of lithium dendrites. In addition, since polyether (such as PDOL) is a chain structure, the crystallinity is high, the chain movement is hindered, the ionic conductivity is low, and the mechanical strength is low. Most importantly, the long chain structure of polyether is easy to decompose under high pressure and cannot match the high-voltage positive electrode with high specific capacity (such as nickel-cobalt-manganese ternary material NCM and lithium cobalt oxide, etc.). In the prior art, different polyether chain structures are often connected to form a network structure by a cross-linking agent (such as trimethylolpropane triglycidyl ether), thereby reducing the crystallinity, increasing the ionic conductivity, and improving the mechanical strength, but the improvement effect is limited and it is difficult to adjust the solvation structure in the battery, and it is impossible to fundamentally solve the problem that the electrochemical stability of polyether-based solid polymer electrolytes is low and difficult to apply under high pressure conditions. Summary of the invention

[0004] The purpose of the present invention is to provide a fluorine-containing cross-linked solid polymer electrolyte, a lithium battery and a preparation method thereof. By adding a fluorine-containing cross-linking agent to form a three-dimensional network structure and aggregated ion pairs in the electrolyte, and highly phase-separated from solvent molecules, improvements in ionic conductivity, mechanical properties and high-voltage stability are achieved, and the problem that the existing polyether network structure has low electrochemical stability and is difficult to match with a high-voltage positive electrode is solved.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A fluorine-containing cross-linked solid polyether electrolyte is prepared from an electrolyte comprising a polymer monomer having an alkylene oxide functional group, a fluorine-containing cross-linking agent, a lithium salt, and an initiator. The fluorine-containing cross-linking agent and the polymer monomer having an alkylene oxide functional group in the electrolyte are in situ polymerized to form a solid electrolyte with a three-dimensional network structure of the fluorine-containing cross-linking agent, wherein the fluorine-containing cross-linking agent is 2,2'-(2,2,3,3,4,4,5,5-octafluorohexane-1,6-diyl)bis(ethylene oxide).

[0007] Specifically, the volume ratio of the polymer monomer having an alkylene oxide functional group to the fluorine-containing crosslinking agent is 1-2:0.1-1.

[0008] The lithium salt includes, but is not limited to, one or more of lithium bis(trifluorosulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonate (LiOTf), and lithium difluorooxalatoborate (LiDFOB). The concentration of the lithium salt in the polymer monomer having an alkylene oxide functional group is 1-3 mol / L.

[0009] The polymer monomer with an alkylene oxide functional group can form a polyether chain by ring-opening polymerization, and the fluorine-containing crosslinking agent connects different polyether chains to form a three-dimensional network structure. The polymer monomer with an alkylene oxide functional group includes but is not limited to one or more of 1,3-dioxolane (DOL), 1,2-butylene oxide, propylene oxide, ethylene oxide, 1,4-dioxane, 1,2-epoxycyclopentene, and 3,4-epoxy-1-butene.

[0010] Furthermore, the initiator can induce the ring-opening polymerization of the polymer monomer with the epoxyalkyl functional group to form a polyether chain. The initiator includes, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorooxalate borate (LiDFOB), aluminum trifluoromethanesulfonate (AI(OTF)3), tin trifluoromethanesulfonate (Sn(OTF)3) and tin difluoride (SnF2). The concentration of the initiator in the polymer monomer with the epoxyalkyl functional group is 0.1mmol / L to 1mol / L.

[0011] Furthermore, the electrolyte also includes a solvent to increase the solubility of the lithium salt in the polymer monomer having an alkylene oxide functional group, thereby further increasing the ionic conductivity of the electrolyte. The solvent is added as needed. The solvent includes but is not limited to one or more of dimethoxymethane (DMM), ethylene glycol dimethyl ether (DME), 1,2-diethoxyethane (DEE), 1,2-dimethoxypropane (DMP) and diphenoxymethane (DH). The volume ratio of the polymer monomer having an alkylene oxide functional group to the solvent is 1 to 2:0-2.

[0012] A method for preparing a fluorine-containing cross-linked solid polyether electrolyte comprises the following steps: in an inert atmosphere, a polymer monomer having an alkylene oxide functional group, a fluorine-containing cross-linking agent, a lithium salt, and an initiator are stirred at room temperature to form a uniform electrolyte, and the electrolyte is polymerized in situ to generate a fluorine-containing cross-linked solid polyether electrolyte.

[0013] Preferably, the in-situ polymerization reaction temperature is 20 to 120° C. and the reaction time is 60 to 300 min.

[0014] A solid-state lithium battery comprises a positive electrode, a fluorine-containing cross-linked solid polyether electrolyte and a negative electrode. An electrolyte for preparing a fluorine-containing cross-linked solid polyether electrolyte is placed in a battery housing equipped with a positive electrode and a negative electrode, and the electrolyte is polymerized and solidified in situ to obtain a solid-state lithium battery. The solid polymer electrolyte using in-situ polymerization is very suitable for modern battery preparation technology and is expected to further promote the industrialization of lithium metal batteries.

[0015] The positive electrode includes an active material, a binder, and a conductive agent. The active material, the binder, and the conductive agent are ground and dissolved in an appropriate amount of solvent N-methylpyrrolidone (NMP) to obtain a uniformly mixed slurry, wherein the active material includes but is not limited to lithium cobalt oxide (LCO), ternary material (NCM), lithium nickel cobalt aluminum oxide (NCA) or lithium iron phosphate (LiFePO4), the binder includes but is not limited to one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), and polyvinyl alcohol (PVA), and the conductive agent includes but is not limited to one or more of conductive carbon black (Super P), acetylene black, Ketjen black, carbon nanotubes, graphene, and conductive graphite.

[0016] The negative electrode is lithium metal, single crystal silicon, silicon monoxide or a silicon-carbon composite material.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The three-dimensional network structure formed by cross-linking the fluorinated cross-linking agent and the polyether chain will lock the molecular monomers, preventing direct contact with the positive and negative electrodes, thereby improving the electrochemical window of the electrolyte;

[0019] (2) Compared with other cross-linking agents, the fluorinated cross-linking agent of the present invention can not only cross-link with the polyether chain to form a three-dimensional network structure, but more importantly, the F atom with stronger electronegativity will pull the electrons of the surrounding O atoms to the F atom, weakening the electronegativity of O and thus weakening the Li + The molecular interaction with the polyether chain provides a faster lithium ion migration channel, achieving an ion conductivity greater than 1mS / cm and a Li+ / -0.85 at room temperature. + Migration number;

[0020] (3) The three-dimensional network structure formed by the present invention has higher mechanical strength and effectively inhibits the penetration of lithium dendrites from the perspective of physical barrier. + The migration number can ensure that Li + The deposition is more uniform, which greatly reduces the influence of concentration polarization caused by the migration of anions together (low migration number), inhibits lithium dendrites from the perspective of chemical reaction, solves the problem of negative electrode dendrite growth piercing the diaphragm and causing battery short circuit in traditional lithium metal batteries, and prolongs battery life;

[0021] (4) Compared with conventional crosslinking agents, the fluorinated crosslinking agent used in the present invention can adjust the solvation structure in the solid polymer electrolyte, specifically: by forming polymer chains and Li + The weak coordination effect between them makes more anions in the system interact with Li + Coordination forms a clustered ion pair structure. In the formation process of SEI (solid electrolyte interface) and CEI (cathode electrolyte interface), more anions are reduced to form inorganic-rich SEI / CEI. The inorganic SEI has stronger conductivity and can prevent further decomposition of the electrolyte at high voltage.

[0022] (5) Compared with conventional cross-linking agents, the polymer chains formed in situ on the cathode and anode surfaces of the battery are highly phase-separated from the solvent molecules and can be used as a solvent-repellent layer to inhibit the continuous side reactions of the solvent with the electrode under high voltage, thereby improving the stability of the electrolyte under high voltage and matching the high-voltage positive electrode. The assembled NCM523||Li battery cycled more than 320 times at a high cut-off voltage of 4.3V with a capacity retention rate of 96.3%, which is also suitable for many other types of high-voltage positive electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a photo of the solid polymer electrolyte of Example 1.

[0024] Figure 2 These are Fourier transform infrared test images of the solid polymer electrolytes of Example 1 and Comparative Example 1.

[0025] Figure 3 Graphs showing the ionic conductivity of the solid polymer electrolytes of Example 1 and Comparative Example 1.

[0026] Figure 4 is the Li of the solid polymer electrolyte of Example 1 and Comparative Example 1 + Migration number graph.

[0027] Figure 5 This is a Li||Li battery cycle performance diagram of Example 1 and Comparative Example 1.

[0028] Figure 6 Surface morphology of lithium metal after cycling of the Li||Li batteries of Example 1 and Comparative Example 1.

[0029] Figure 7 This is a graph showing the cycle performance of the solid polymer electrolyte lithium metal full battery of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0031] Example 1

[0032] (1) Preparation of fluorine-containing electrolyte: DOL, fluorine-containing crosslinker, and DME were weighed and mixed in a glove box in a volume ratio of 1:0.5:2, 1 mol / L of LiDFOB and 1 mol / L of LiTFSI were added, and the obtained precursor solution was continuously stirred for 0.5 hours at room temperature to form a uniform electrolyte solution, wherein the fluorine-containing crosslinker was 2,2'-(2,2,3,3,4,4,5,5-octafluorohexane-1,6-diyl)bis(ethylene oxide). The above electrolyte was used to assemble a symmetric cell and a full cell according to steps (2) and (3) respectively.

[0033] (2) Assembling a symmetrical battery: Select lithium metal sheets as positive and negative electrodes and assemble the battery together with the electrolyte solution in step (1).

[0034] (3) Assemble the full battery:

[0035] (301) Preparation of the positive electrode: NCM523, Super P, and PVDF were weighed and ground into a uniform mixture at a ratio of 8:1:1. An appropriate amount of NMP was added and stirred to obtain a slurry, which was then evenly coated on aluminum foil. The coated electrode was transferred to an oven for drying, cut into discs with a diameter of 10 mm, and stored in a glove box for later use.

[0036] (302) Assemble button cells using the electrolyte of step (1). The specific process of assembling the cells is as follows: assemble the CR2032 button cells in the following order: positive electrode shell, positive electrode, electrolyte, separator, electrolyte, negative electrode (lithium metal sheet), gasket, spring and negative electrode shell.

[0037] (4) High temperature curing: The battery obtained in steps (2) and (3) is cured at 50° C. for 200 min. The F-PDOL solid polymer electrolyte and the corresponding battery are obtained by high temperature curing.

[0038] Comparative Example 1

[0039] According to step (1) of Example 1, DOL, DME, LiDFOB and LiTFSI were weighed and mixed in a glove box at a volume ratio of 1:2:1:1, without adding a fluorine-containing crosslinking agent, and the other steps were the same as Example 1. The PDOL solid polymer electrolyte and the corresponding lithium battery were obtained by high temperature curing.

[0040] 1. Appearance and infrared testing (FTIR)

[0041] After the electrolyte of Example 1 was solidified, the results were as follows Figure 1 As shown, the electrolyte is transparent before polymerization, and is white in color after polymerization.

[0042] Perform Fourier transform infrared test, the results are as follows Figure 2 The weakening of the CH out-of-plane vibration peak of the DOL molecule and the enhancement of the peak of the formed long chain indicate that polymerization reaction has occurred in Example 1 compared with Comparative Example 1.

[0043] 2. Ionic conductivity and Li + Migration number

[0044] Ionic conductivity and Li + Migration number Figure 3 , 4 As shown, an ionic conductivity greater than 1 mS / cm and a Li+ / - of 0.85 were achieved at room temperature. + The migration number of the comparative example 1 is less than 1mS / cm at room temperature. + The migration number is only 0.29, indicating that the formed fluorinated polymer electrolyte provides a faster lithium ion migration channel.

[0045] 3. Symmetrical battery long cycle performance and scanning electron microscopy (SEM)

[0046] The long cycle performance of the Li||Li battery obtained in Example 1 and Comparative Example 1 is as follows Figure 5 Example 1 at 0.2 mA cm -2 The battery can be cycled stably for more than 3000 hours and maintain a low overpotential. In contrast, in Example 1, the battery short-circuited after 200 hours due to the side reaction at the electrode / electrolyte interface. The lithium sheet was removed from the cycled Li||Li battery and the lithium salt on the surface was washed off with DME solvent for sample preparation and observation. The microscopic surface and cross-sectional morphology obtained are as follows: Figure 6As shown in the figure, it can be seen that the surface morphology of Example 1 is smoother and flatter than that of Comparative Example 1, indicating that the formed fluorine-containing polymer electrolyte can inhibit the growth and deposition of lithium dendrites.

[0047] 4. NCM523||Li battery cycle performance test

[0048] The LandCT3002A battery testing system was used to test the charge and discharge performance of the button batteries assembled above at room temperature.

[0049] Figure 7 The figure is a graph of lithium metal battery cycle performance. The NCM523||Li battery of Example 1 cycles more than 320 times at a cut-off voltage of 4.3V, and the capacity retention rate is 96.3%. However, the comparative example 1 has a short circuit after 120 cycles. This shows that Example 1 can match the high-voltage positive electrode and has higher high-voltage resistance than the comparative example 1.

[0050] Example 2

[0051] (1) Preparation of fluorine-containing electrolyte: 1,2-butylene oxide, fluorine-containing crosslinking agent and DEE were weighed and mixed in a glove box in a volume ratio of 1.5:0.5:1, 0.5 mol / L of LiPF6 and 1.5 mol / L of LiFSI were added, and the obtained precursor solution was continuously stirred at room temperature for 0.5 hour to form a uniform electrolyte solution, wherein the fluorine-containing crosslinking agent was 2,2'-(2,2,3,3,4,4,5,5-octafluorohexane-1,6-diyl)bis(ethylene oxide).

[0052] (2) Assembling a symmetrical battery: Select lithium metal sheets as positive and negative electrodes and assemble the battery together with the electrolyte solution in step (1).

[0053] (3) High temperature curing: The battery obtained in step (2) was cured by heating at 60° C. for 200 min.

[0054] The Li||Li symmetric battery in this embodiment has a -2 It can cycle for more than 2000 hours at a current density of , and has good cycle stability performance.

[0055] Example 3

[0056] (1) Preparation of fluorine-containing electrolyte: Propylene oxide, fluorine-containing crosslinking agent and DMM were weighed and mixed in a glove box in a volume ratio of 1.7:0.3:1, 0.5 mol / L LiBF4 and 2 mol / L LiTFSI were added, and the obtained precursor solution was continuously stirred at room temperature for 1 hour to form a uniform electrolyte solution, wherein the fluorine-containing crosslinking agent was 2,2'-(2,2,3,3,4,4,5,5-octafluorohexane-1,6-diyl)bis(ethylene oxide).

[0057] (2) Preparation of battery positive electrode: NCM811, carbon nanotubes and PAA were weighed and ground in a ratio of 8:1:1, and mixed evenly. A proper amount of NMP was added and stirred evenly to obtain a slurry, which was evenly coated on aluminum foil. The coated electrode was then transferred to an oven for drying, cut into discs with a diameter of 10 mm and stored in a glove box for later use.

[0058] (3) Assembling the whole battery: Assemble the button cell using electrolyte. The specific process of assembling the battery is as follows: Assemble the CR2032 button cell in the order of positive electrode shell, positive electrode, electrolyte, diaphragm, electrolyte, negative electrode (lithium metal sheet), gasket, spring and negative electrode shell.

[0059] (4) High temperature curing: The battery obtained in step (4) was cured by heating at 60° C. for 150 min.

[0060] The NCM811 full battery of this embodiment was cycled more than 300 times at a high cut-off voltage of 4.5V, with a capacity retention rate of 93.63%, and had good high-voltage resistance.

Claims

1. A fluorinated cross-linked solid polyether electrolyte, characterized in that: The invention is prepared from an electrolyte including a polymer monomer having an alkylene oxide functional group, a fluorine-containing crosslinking agent, a lithium salt, and an initiator. The fluorine-containing crosslinking agent and the polymer monomer having an alkylene oxide functional group in the electrolyte are in situ polymerized to form a solid electrolyte with a three-dimensional network structure of the fluorine-containing crosslinking agent, wherein the fluorine-containing crosslinking agent is 2,2'-(2,2,3,3,4,4,5,5-octafluorohexane-1,6-diyl)bis(ethylene oxide).

2. The fluorinated cross-linked solid polyether electrolyte according to claim 1, characterized in that: The volume ratio of the polymer monomer with epoxyalkyl functional groups to the fluorine-containing crosslinking agent is 1-2:0.1-1; the concentration of the lithium salt in the polymer monomer with epoxyalkyl functional groups is 1-3 mol / L; the concentration of the initiator in the polymer monomer with epoxyalkyl functional groups is 0.1 mmol / L-1 mol / L.

3. The fluorinated cross-linked solid polyether electrolyte according to claim 1, characterized in that: The lithium salt includes one or more of lithium bis(trifluorosulfonyl)imide, lithium bis(fluorosulfonate)imide, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium trifluoromethanesulfonate, and lithium difluorooxalatoborate.

4. The fluorinated cross-linked solid polyether electrolyte according to claim 1, characterized in that: The polymer monomer having an alkylene oxide functional group includes one or more of 1,3-dioxolane (DOL), 1,2-butylene oxide, propylene oxide, ethylene oxide, 1,4-dioxane, 1,2-epoxycyclopentene, and 3,4-epoxy-1-butene.

5. The fluorinated cross-linked solid polyether electrolyte according to claim 1, characterized in that: The initiator includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, aluminum trifluoromethanesulfonate, tin trifluoromethanesulfonate and tin difluoride.

6. The fluorinated cross-linked solid polyether electrolyte according to claim 1, characterized in that: The electrolyte also includes a solvent, and the volume ratio of the polymer monomer having an alkylene oxide functional group to the solvent is 1-2:0-2.

7. The fluorinated cross-linked solid polyether electrolyte according to claim 6, characterized in that: The solvent includes one or more of dimethoxymethane, ethylene glycol dimethyl ether, 1,2-diethoxyethane, 1,2-dimethoxypropane and diphenoxymethane.

8. The method for preparing the fluorinated cross-linked solid polyether electrolyte according to any one of claims 1 to 7, characterized in that: Under an inert atmosphere, a polymer monomer having an alkylene oxide functional group, a fluorine-containing crosslinking agent, a lithium salt and an initiator are stirred at room temperature to form a uniform electrolyte, and the electrolyte is polymerized in situ to generate a fluorine-containing crosslinked solid polyether electrolyte.

9. A solid-state lithium battery, characterized in that: The invention comprises a positive electrode, a fluorine-containing cross-linked solid polyether electrolyte and a negative electrode. The electrolyte for preparing the fluorine-containing cross-linked solid polyether electrolyte is placed in a battery shell equipped with the positive electrode and the negative electrode, and the electrolyte is polymerized and solidified in situ to obtain a solid lithium battery.

10. A solid-state lithium battery, characterized in that: The positive electrode includes an active material, a binder, and a conductive agent, wherein the active material includes lithium cobalt oxide, a ternary material, lithium nickel cobalt aluminum oxide, or lithium iron phosphate.

Citation Information

Cited By

  • In-situ cross-linked flame-retardant polymer electrolyte and precursor solution and battery thereof

    CN121149395A